2014
DOI: 10.1007/s12565-014-0251-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiological and morphologic assessments of myocardial bridges

Abstract: In this study we aimed to compare the findings of coronary dual-source computed tomography angiography of myocardial bridges with cadaveric dissections. Forty-one isolated, non-damaged fresh sheep hearts were used in this study. Myocardial bridges of the anterior interventricular branch of the left coronary artery were demonstrated and analyzed by a coronary dual-source computed tomography angiography. Dissections along the left anterior interventricular branch of the left coronary artery were performed by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
1
4
0
1
Order By: Relevance
“…Our study showed that a “typical” myocardial bridge has around 19 mm in length and 2.5 mm in thickness, values that can be considered hemodynamically significant . If, however, for prevalence data we believed that this meta‐analysis underestimated the true prevalence of this variant, for the analyses of mean thickness and length we believe the mean values are in reality lower, as more superficial and/or smaller bridges are less likely to be detected by using imaging techniques, a hypothesis confirmed by other studies . Ercakmak, for example, found the length of the MB, as assessed during autopsy to be significantly higher compared to the one assessed using CT (a mean increase of 4.5 mm) .…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Our study showed that a “typical” myocardial bridge has around 19 mm in length and 2.5 mm in thickness, values that can be considered hemodynamically significant . If, however, for prevalence data we believed that this meta‐analysis underestimated the true prevalence of this variant, for the analyses of mean thickness and length we believe the mean values are in reality lower, as more superficial and/or smaller bridges are less likely to be detected by using imaging techniques, a hypothesis confirmed by other studies . Ercakmak, for example, found the length of the MB, as assessed during autopsy to be significantly higher compared to the one assessed using CT (a mean increase of 4.5 mm) .…”
Section: Discussionsupporting
confidence: 75%
“…Ercakmak, for example, found the length of the MB, as assessed during autopsy to be significantly higher compared to the one assessed using CT (a mean increase of 4.5 mm) (141). There were no differences regarding the depth (141), most likely due to an incomplete identification of superficial bridges during CT examination (141). Evaluating the hemodynamic significance of MB was beyond the purpose of this analysis.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Ercakmak et al. (2015) have compared the findings of coronary dual‐source computed tomography angiography of myocardial bridges with cadaveric dissections. The results have shown that coronary computed tomography angiography is reliable in evaluating the presence and depth of myocardial bridges.…”
Section: Introductionmentioning
confidence: 99%
“…Глубина залегания ММ, по данным КТ-коронарографии, колебалась в диапазоне от 0,4 до 7,4 мм, на аутопсийном материале этот показатель не превышал 10 мм. При этом следует иметь в виду, что реальные морфометрические параметры ММ всегда больше его протяженности, измеряемой на МСКТ-сканах [24]. Различия могут достигать 4,5 мм.…”
unclassified